Characterization of Coloured Sorghum Genotypes for Qualitative and Quantitative Characters - Kumar, Akshay; Suvarna; Kuchanur, P. H.; Girish, G.; Lakshmikanth, M. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted at College of Agriculture, Raichur, University of Agricultural Sciences, Raichur, Karnataka, India during October 2021–Februrary 2022 to characterize the 100-coloured sorghum genotypes along with four checks viz., M 35-1, AKJ 1, Paiyur 2 and GS-23 for eight qualitative characters and 10 quantitative characters in an augmented block design. The results revealed that, majority of the genotypes exhibited the pigmented stem (93%) and leaves almost green (61%) at harvest, horizontal flag leaf orientation (100%), loose erect primary branches of panicle (38%), black glumes (58%), red grain colour (36%), circular grain shape (75%) and freely threshable (93%) characters. For all the quantitative characters studied, a wide range of variation was observed. For stay green character, genotype IS 21868 showed completely green leaves. Similarly, for other characters also superior genotypes were identified in this study. Such genotypes can be used further in improvement of sorghum for its grain yield. For grain yield, 14 genotypes exhibited higher yields when compared to the best check GS-23, viz., IS 29032 (120.0 g), IS 6508 (119.18 g), IS 16006 (113.80 g), IS 28065 (102.88 g), IS 23890 (94.88 g), IS 28049 (94.28 g), IS 23865 (89.48 g), IS 29031 (87.98), IS 28202 (87.88), IS 31706 (86.48), IS 2582 (85.88 g), IS 28200 (83.58), IS 16398 (81.08 g) and IS 23955 (80.0 g). Eight genotypes were on par with GS-23. These genotypes can be further evaluated for its yield stability within and across locations.